Analisis Kesiapan Pengembangan Rekam Medis Elektronik Menggunakan DOQ-IT di RS “X” Yogyakarta - Kori Puspita Ningsih; Suryo Nugroho Markus; Ngatoiatu Rahmani; Ida Nursanti (Indonesian of Health Information Management Journal (INOHIM), 2023)
AbstractMedical records are a vital part of the evidence for recording patient examinations. Several middle and high-income countries have implemented Electronic Medical Records (RME) to support patient health documentation. The development of RME in Indonesia has been regulated in the Minister of Health Regulation 24 of 2022. Hospital "X" Yogyakarta is starting to develop RME but has not yet developed a strategic plan for developing RME. Without a clear plan, developing RME at Hospital "X" Yogyakarta seems patchy. Therefore, in developing RME, it is necessary to analyze the hospital's readiness first. This research uses analytical observational research with a mixed-method data collection approach. This study uses an adequate instrument to analyze healthcare facilities' readiness to implement EHR using the DOQ-IT approach. The analysis of RME development readiness results from human resources, leadership, organizational culture, and infrastructure components at the "X" Hospital Yogyakarta. Analysis of the scores of the four components of 76.48 with an average value of 2.64. The assessment results show that RS "X" Yogyakarta is ready to develop RME. The readiness to develop RME is strong at RS "X" Yogyakarta, supported by strengths in organizational work culture, leadership and infrastructure, but also weaknesses in human resources. Therefore, RS "X" Yogyakarta needs to provide training and increase motivation so that human resources are far ready for RME development.Keywords: readiness, DOQ-IT, EMR AbstrakRekam medis merupakan bagian vital dalam bukti pencatatan pemeriksaan pasien. Beberapa negara berpenghasilan menengah dan tinggi, telah menerapkan Rekam Medis Elektronik (RME) untuk mendukung dokumentasi kesehatan pasien. Pengembangan RME di Indonesia telah diatur pada Permenkes 24 Tahun 2022. RS “X” Yoyakarta muai mengembangkan RME, namun belum menyusun rencana srategi pengembangan RME. Dalam pengembangan RME diperlukan perencanaan yang matang, sehingga rumah sakit bisa menilai sejauh mana kesiapan untuk memulai tahap pengembangan RME. RS “X” Yogyakarta sudah mengembangkan RME, namun masih terkesan tambal sulam. Penelitian ini bertujuan untuk menganalisis kesiapan pengembangan RME menggunakan pendekatan DOQ-IT. Penelitian ini menggunakan observational analitik. dengan pendekatan pengumpulan data mixed methode. Pada penelitian ini menggunakan instrumen yang efektif untuk menganalisis kesiapan fasilitas pelayanan kesehatan dalam melaksanakan EHR menggunakan pendekatan DOQ-IT. Hasil analisis kesiapan pengembangan RME dari komponen sumberdaya manusia, kepemimpinan, budaya organisasi, dan infrastruktur di RS “X” Yogyakarta. Analisis skor dari keempat komponen sebesar 76,48 dengan rata-rata nilai sebesar 2,64. Dari hasil penilaian tersebut menunjukkan RS “X” Yogyakarta cukup siap dalam mengembangkan RME. Kesiapan pengembangan RME kuat di RS “X” Yogyakarta   didukung dengan adanya kekuatan di budaya kerja orgnanisasi, kepemimpinan dan infrastruktur, akan tetapi juga memiliki kelemahan di SDM. Oleh karena itu RS “X” Yogyakarta perlu memberikan pelatihan dan meningkatkan motivasi supaya SDM menjadi jauh siap dalam pengembangan RME.Kata Kunci: kesiapan, DOQ-IT, rekam medis elektronik